Ultrafast, high modulation depth terahertz modulators based on carbon nanotube thin films. (March 2021) - Burdanova, Maria G.; Katyba, Gleb M.; Kashtiban, Reza; Komandin, Gennady A.; Butler-Caddle, Edward; Staniforth, Michael; Mkrtchyan, Aram A.; Krasnikov, Dmitry V.; Gladush, Yuriy G.; Sloan, Jeremy; Nasibulin, Albert G.; Lloyd-Hughes, James
Abstract: The development of THz technology and communication systems is creating demand for devices that can modulate THz beams rapidly. Here we report the design and characterisation of high-performance, broadband THz modulators based on the photo-induced transparency of carbon nanotube films. Rather than operating in the standard modulation mode, where optical excitation lowers transmission, this new class of modulators exhibits an inverted modulation mode with an enhanced transmission. Under femtosecond pulsed illumination, modulation depths reaching + 80 % were obtained simultaneously with modulation speeds of 340 GHz. The influence of the film thickness on the insertion loss, modulation speed and modulation depth was explored over a frequency range from 400 GHz to 2.6 THz. The excellent modulation depth and high modulation speed demonstrated the significant potential of carbon nanotube thin films for ultrafast THz modulators. Graphical abstract: Image 1